Secrets of great teachers : 22 strategies to energize middle and high school classrooms - Zeffren, Elisheva
"You can abandon rote learning with this middle and high school teaching guide. Encouraging both students and teachers to unlock their creativity. This book leads teachers away from endorsing competition and teacher-pleasing behavior, and offers ideas for independent thinking that will strengthen students' decision-making, deductive reasoning and emotional intelligence"--